Matrix converter open circuit behavior analysis - Zhang, Jiawei; Brunson, Christopher; Bowden, James; Wheeler, Patrick; De Lillo, Liliana (2016)
The matrix converter current recirculating path during an open circuit condition is given in detail with the aim of contributing more expert knowledge to a fault detection system for matrix converter. Simulation results were obtained demonstrating how current recirculates in the matrix converter and the clamp circuit during an open-circuit fault. Healthy output phase currents can be canceled to zero due to current recirculating via the clamp circuit. This result could contribute expert knowledge to a fault detection system to avoid false fault detection and diagnosis.